2020
DOI: 10.1002/glia.23791
|View full text |Cite
|
Sign up to set email alerts
|

Microglial responses after phagocytosis: Escherichia coli bioparticles, but not cell debris or amyloid beta, induce matrix metalloproteinase‐9 secretion in cultured rat primary microglial cells

Abstract: Upon infection or brain damage, microglia are activated to play roles in immune responses, including phagocytosis and soluble factor release. However, little is known whether the event of phagocytosis could be a trigger for releasing soluble factors from microglia. In this study, we tested if microglia secrete a neurovascular mediator matrix metalloproteinase-9 (MMP-9) after phagocytosis in vitro. Primary microglial cultures were prepared from neonatal rat brains. Cultured microglia phagocytosed Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…The activation of TLR4 and its downstream pathway could promote the activation of microglia and facilitate the release of inflammatory factors in the brain (Leitner et al, 2019). Furthermore, previous studies have shown that the intestinal flora metabolite LPS is a vital activator of TLR4 that can specifically binds to TLR4 and activates its downstream proinflammatory signaling pathway (Kinsner et al, 2006;Hamanaka et al, 2020). Accordingly, we hypothesize that HF could facilitate intestinal barrier dysfunction and increase the release of LPS, which could further activate TLR4 and promote neuroinflammation.…”
Section: Introductionmentioning
confidence: 94%
“…The activation of TLR4 and its downstream pathway could promote the activation of microglia and facilitate the release of inflammatory factors in the brain (Leitner et al, 2019). Furthermore, previous studies have shown that the intestinal flora metabolite LPS is a vital activator of TLR4 that can specifically binds to TLR4 and activates its downstream proinflammatory signaling pathway (Kinsner et al, 2006;Hamanaka et al, 2020). Accordingly, we hypothesize that HF could facilitate intestinal barrier dysfunction and increase the release of LPS, which could further activate TLR4 and promote neuroinflammation.…”
Section: Introductionmentioning
confidence: 94%
“…For example, LPS released by gut bacteria can breakdown the BBB and increase its permeability ( 29 ). Moreover, LPS can bind to the TLR4 to induce monocyte differentiation into M1-type microglia and activate microglia to express nitric oxide and pro-inflammatory cytokines by activating the TLR4 signaling ( 8 , 30 ). Evidently, intraperitoneal injections with LPS induced microglia activation and neuroinflammation in CNS in rats ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in pathological state, the imbalance of gut microbial compositions and the damages of gut barrier can produce and allow more harmful products into the systemic circulation ( 7 ). This process can further impair the BBB function and activate microglia, leading to neuroinflammation ( 8 ). Interestingly, recent studies have also reported intestinal dysfunction and microbiota imbalance in cardiovascular diseases ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, LPS released by gut bacteria can breakdown the BBB and increase its permeability (29). Moreover, LPS can bind to the TLR4 to induce monocyte differentiation into M1-type microglia and activate microglia to express nitric oxide and pro-inflammatory cytokines by activating the TLR4 signaling (8,30). Evidently, intraperitoneal injections with LPS induced microglia activation and neuroinflammation in CNS in rats (39).…”
Section: Gut-brain Axis and Neuroinflammationmentioning
confidence: 99%
“…However, in pathological state, the imbalance of gut microbial compositions and the damages of gut barrier can produce and allow more harmful products into the systemic circulation (7). This process can further impair the BBB function and activate microglia, leading to neuroinflammation (8). Interestingly, recent studies have also reported intestinal dysfunction and microbiota imbalance in cardiovascular diseases (9).…”
Section: Introductionmentioning
confidence: 99%